Case Study on Improving Orientation and Mobility Skills of Students with Visual Impairments in the School Environment without Using a Cane - Mayanti, Serli; Utami, Ratna Tri; Maisuhetni, Maisuhetni (Universitas Sang Bumi Ruwa Jurai, 2025)
Students with visual impairments often face challenges in performing orientation and mobility (O&M) activities independently, particularly without assistive tools such as canes. In the school environment, these skills are essential to ensure safety, spatial awareness, and confidence. This study aims to explore the teacher's strategies in enhancing the O&M skills of a visually impaired student within a school setting without relying on a cane. Employing a qualitative approach with a case study design, data were collected through observations, interviews, and documentation involving a Grade VII student and a classroom teacher at SLB A Bina Insani. The findings reveal that the teacher served as a facilitator, motivator, and primary trainer by applying gradual, structured training methods, including step-counting, spatial orientation, sensory exploration, and route repetition. As a result, the student demonstrated significant improvement in navigating the school environment confidently and independently without a cane. This study highlights the importance of teacher involvement and adaptive strategies in fostering mobility independence among students with visual impairments.